2013
DOI: 10.1021/pr400859w
|View full text |Cite
|
Sign up to set email alerts
|

Low- and High-Grade Bladder Cancer Determination via Human Serum-Based Metabolomics Approach

Abstract: To address the shortcomings of urine cytology and cystoscopy for probing and grading urinary bladder cancer (BC), we applied (1)H nuclear magnetic resonance (NMR) spectroscopy as a surrogate method for the identification of BC. This study includes 99 serum samples comprising low-grade (LG; n = 36) and high-grade (HG; n = 31) BC as well as healthy controls (HC; n = 32). (1)H NMR-derived serum data were analyzed using orthogonal partial least-squares discriminant analysis (OPLS-DA). OPLS-DA-derived model validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 69 publications
2
67
0
Order By: Relevance
“…NMR analytics have been used for biomarker detection in humans in several tumor entities other than PCa (Table 2): non-small-cell lung cancer (Doskocz et al, 2015), oral squamous cell carcinoma (OSCC) , gastric cancer (Jung et al, 2014), myeloma (Lodi et al, 2013), pancreatic ductal adenocarcinoma (Davis et al, 2013), lung cancer (Carrola et al, 2011), and BCa (Bansal et al, 2013).…”
Section: Prostate Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…NMR analytics have been used for biomarker detection in humans in several tumor entities other than PCa (Table 2): non-small-cell lung cancer (Doskocz et al, 2015), oral squamous cell carcinoma (OSCC) , gastric cancer (Jung et al, 2014), myeloma (Lodi et al, 2013), pancreatic ductal adenocarcinoma (Davis et al, 2013), lung cancer (Carrola et al, 2011), and BCa (Bansal et al, 2013).…”
Section: Prostate Cancermentioning
confidence: 99%
“…One study on serum 1 H-NMR revealed good separation of low-and high-grade BCa from healthy controls (AUC 0.95, sensitivity 96% and specificity 94%) (Bansal et al, 2013). A panel of six metabolites (dimethylamine (DMA), malonate, lactate, glutamine, histidine, and valine) was derived from the orthogonal projection to latent structure discriminant analysis (OPLS-DA) model.…”
Section: Bladder Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…While glycerophosphocholines, linoleic acid, oleic acid and arachidonic acid were demonstrated to be elevated in bladder cancer tissue, sphingomyelin was only found in normal bladder tissue (Table 1). In a study conducted by Bansal et al [14], serum metabolism profiling of 36 low grades BC and 32 high grades BC patients were compared with 32 healthy subjects using H-NMR analytical method. Malonate level was found significantly higher in patients with BC.…”
Section: Introductionmentioning
confidence: 99%
“…These changes can be observed in the metabolite profiles by NMR or MS and metabolite biomarkers can be identified [1][2][3][4][5][6][7]. High-Resolution Magic Angle Spinning (HRMAS) NMR has been used to study prostate cancer tissues and cells with much successfulness since its introduction in the late 1990s [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%